Application of Tracer Isotopes in Kinetic Study of First Order Ion Exchange Reaction - Lokhande, R.S.; R.D. Tiwari, Santoshi (Asian Journal of Chemistry, 2010)
Analysis of first order ion exchange reaction rates at different temperatures [27°C to 50°C] and particularly at low concentration of KBr solution [electrolyte] ranging from 0.005 M to 0.1 M has been carried out by application of radioactive tracer isotope 82Br with increase in concentration of electrolyte. Amounts of bromide ion exchanged in millimoles increases specific reaction rates of ion exchange reaction and are calculated for different temperatures and for different amounts of ion exchange resins. It is observed that with increase in temperature reaction rate increases but the increase is more pronounced for increase in amount of ion exchange resins. For 0.005 M solution of electrolyte, the reaction rate increases from 0.120 min-1 at 27°C to 0.209 at 50°C. For 0.005 M solution of electrolyte at 27°C reaction rate increases from 0.120 min -1 for 1.0 g of resin to 0.190 min-1 for 5.0 g of resin. From the reaction rate calculated at different temperatures energy of activation in KJ/mole is calculated. It is observed that for 0.005M solution of electrolyte, energy of activation is 6.801 kJ/mole which decreases to 6.120 kJ/mole for increase in concentration of electrolyte to 0.100 M.